Performance evaluation of CNC turning process for tool tip temperature and tool wear by Taguchi method. (2022) - Kamble, Prashant D.; Waghmare, Atul C.; Askhedkar, Ramesh D.; Sahare, Shilpa B.; Patil, Manoj; Prayagi, Sunil V.
Abstract: The performance of the CNC turning process is experimentally evaluated in this paper. The independent variables are feed rate, depth of cut, nose radius, tool type, and environmental condition. Three different levels of predictors are selected. The dependent variables are TTT (tool tip temperature) and TW (tool wear). The machine is run at 1337 RPM. The chatter in the spindle is included as an uncontrollable variable (Noise Factor) with three different values. The number of observations is calculated by Taguchi Method. The experimentation is conducted on CNC Spinner Lathe Machine. The responses are measured by a Non-contact laser gun and Canny Method in MATLAB software. The analysis is performed by Taguchi philosophy and ANOVA. The best setting for responses is identified by the main effect plot. The prediction of the output parameters at optimum levels is done by additive model. Minimum Tool Tip Temperature (50.545 °C) is achieved when Environmental condition is at high level (minimum quantity lubrication), Nose Radius is at low level (0.4 mm), Feed rate is at low level (0.15 mm/rev), Depth of cut is at low level (0.5 mm) and tool type is at high level (CVD Coated insert). Minimum Tool Wear (0.0401 mm) is achieved when Environmental condition is at high level (minimum quantity lubrication), Nose Radius is at high level (1.2 mm), Feed rate is at high level (0.35 mm/rev), Depth of cut is at low level (0.5 mm) and tool type is at high level (CVD Coated insert).